2021
DOI: 10.1111/jfbc.13849
|View full text |Cite
|
Sign up to set email alerts
|

Ziziphus spina‐christi (L.) fortified with Camellia sinensis mediates apoptosis, Notch‐1 signaling, and mitigates obesity‐induced non‐alcoholic fatty liver

Abstract: The habit of drinking tea is highly prevalent and could be utilized to introduce more health benefits through fortification with medicinal plants. The purpose of this analysis was to assess the nutritional quality and health benefits of fortified Ziziphus tea (ZT) with green tea (GT) against obesity and non‐alcoholic fatty liver disease (NAFLD). Proximate analysis and sensory evaluation were carried out on the fortified tea. In the in vivo study, 15 SD rats were used for each group. Flow cytometry was utilized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 63 publications
2
8
0
Order By: Relevance
“…This indicates destruction of liver tissue in the group with HFD. This in agreement with the finding of a recent study [20] which recorded that liver enzymes were significantly increased after induction of NAFL in rats. This indicates hepatic destruction in the rat-induced NAFL group.…”
Section: : Photomicrographs Of Immunostained Liver Sections For Caspa...supporting
confidence: 93%
See 1 more Smart Citation
“…This indicates destruction of liver tissue in the group with HFD. This in agreement with the finding of a recent study [20] which recorded that liver enzymes were significantly increased after induction of NAFL in rats. This indicates hepatic destruction in the rat-induced NAFL group.…”
Section: : Photomicrographs Of Immunostained Liver Sections For Caspa...supporting
confidence: 93%
“…The histological examination of liver structure in rat-induced NAFL was also accompanied by changes in lipid profile and liver enzyme. This coincides with the results of recent studies [4], [13], [20].…”
Section: : Photomicrographs Of Immunostained Liver Sections For Caspa...supporting
confidence: 93%
“…Recently, phenolic compounds have been widely studied because of their biological effects, especially antioxidant activity [19,20] . Their ability to donate hydrogen atoms or electrons to free radicals is a crucial function of phenolic compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, phenolic compounds have been widely studied because of their biological effects, especially antioxidant activity. [19,20] Their ability to donate hydrogen atoms or electrons to free radicals is a crucial function of phenolic compounds. A previous study reported that total phenolic and flavonoid contents have high correlations with free radical scavenging activity assessed using Pearson test.…”
Section: Molecular Dockingmentioning
confidence: 99%
“…( 2018 ) showed nuclear factor (erythroid-derived 2)-like 2 (Nrf2) could profoundly ameliorate hepatic lipogenesis and IR by repressing NICD. Besides, researchers also found plant extracts (such as curcumin) have been shown to suppress NOTCH1, which could ameliorate fatty liver and enhance insulin sensitivity in the high-fat diet (HFD) model ( Zhao et al, 2017 ; Saadati et al, 2019 ; El et al, 2021 ).…”
Section: Notch In Insulin Resistancementioning
confidence: 99%